2016
DOI: 10.1248/bpb.b15-00662
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Lipid Excretion after Consumption of a Black Tea Polyphenol Containing Beverage–Randomized, Placebo-Controlled, Double-Blind, Crossover Study–

Abstract: Obesity is a serious medical condition worldwide. Inhibition of lipid absorption is very important in preventing obesity. In a previous study, we found that postprandial elevation of triacylglycerol was suppressed by the intake of black tea polyphenol (BTP). We also reported that BTP caused lipid excretion into feces in an animal study. The present study is a clinical trial that examined lipid excretion. In this randomized, placebo-controlled, double-blind, crossover study, in the first test period participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…It contains polyphenols and other metabolites, with anti-carcinoma (Wang and Bachrach, 2002;Zhang et al, 2012), anti-oxidative (Rietveld and Wiseman, 2003;Fatima and Rizvi, 2015) and anti-arteriosclerosis (Lee et al, 2015) properties. These polyphenols are also reported to be effective for the prevention of Alzheimer's and Parkinson diseases (Mandel, Amit, Weinreb, Reznichenko, and Youdim, 2008;Anandhan, Tamilselvam, Radhiga, Rao, and Essa, 2012) and for their anti-obesity effects in human and animals (Zhong, Furne, and Levitt, 2006;Ashigai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It contains polyphenols and other metabolites, with anti-carcinoma (Wang and Bachrach, 2002;Zhang et al, 2012), anti-oxidative (Rietveld and Wiseman, 2003;Fatima and Rizvi, 2015) and anti-arteriosclerosis (Lee et al, 2015) properties. These polyphenols are also reported to be effective for the prevention of Alzheimer's and Parkinson diseases (Mandel, Amit, Weinreb, Reznichenko, and Youdim, 2008;Anandhan, Tamilselvam, Radhiga, Rao, and Essa, 2012) and for their anti-obesity effects in human and animals (Zhong, Furne, and Levitt, 2006;Ashigai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Green tea appears to be more strongly related to reduced total and LDL cholesterol, as evidenced by a large number of metaanalytical publications [22,23,[36][37][38]. For black tea those with a higher cardiovascular risk appear to have more benefit [11] with indications from RCTs suggesting that black tea could reduce triglyceride levels, alter body fat distribution and increase fat excretion [6,40,44]. For black tea there is evidence that this can improve FMD and exhibit vascular protective properties that could be of clinical relevance [48,49,53].…”
Section: Discussionmentioning
confidence: 99%
“…Bahorun et al [56] hip ratio indicating improved body fat distribution [6]. A small trial comprised of two 10-day intervention periods found that the ingestion of black tea polyphenols (55 mg as a beverage) three times daily increased faecal lipid excretion [40]. Other work using Goishi tea (122 mg polyphenols) found this to increase HDL cholesterol and reduce elevations in triglycerides, especially amongst those with a BMI <25 kg/m 2 after 12 weeks of drinking this [39].…”
Section: Strength and Amount Of Evidence Referencesmentioning
confidence: 99%
See 2 more Smart Citations